Editorial - Deniz Evcik, (Archives of Rheumatology, 2010)
It is a great pleasure to introduce you the new issue of the Turkish Journal of Rheumatology. In this issue, there are 10 interesting papers. As you all know, the EULAR congress was held between 16-21th of June 2010 in Rome. The Turkish League Against Rheumatism (TLAR) broke new ground by having a booth at the EULAR Conference. As the only scientific association that officially represents Turkey in the EULAR, it was a great pleasure to meet so many of our colleagues and international participants that came and visited with us at our booth. It was also a great chance for us to introduce our journal, the Turkish Journal of Rheumatology to many rheumatologists, physiatrists and researchers coming from different parts of the world. We hope to add new members to our International Editorial Board as well as get manuscript submissions from authors worldwide Hereby let me remind you all that the TLAR was established in 1947, the year of EULAR's foundation by Physical and Rehabilitation Medicine specialists in order to stimulate and promote prevention, treatment and rehabilitation of rheumatic diseases as well as to support academic research and scientific meetings in the field of rheumatology. As a 63-year old association, The TLAR wishes to leave a lasting mark on science and society. After a long term and hard working year we wish you all a happy and healthy holiday. Best regards, Deniz Evcik, MD Editor